Critical Opinion Paradigm Regulation of Criminal Actions of Drug Abuse Through Religious Rehabilitation Based on the Legal System - Laksana, Andri Winjaya; Widodo, Hendro; Pramana, Dian (Media Iuris, 2024)
Addicts or users of narcotics are both victims and criminal perpetrators of crimes. All narcotics abusers utilizing criminal provisions are governed by the Article 127 of Law No. 35 of 2009 pertaining to narcotics According to Article 127, those who abuse drugs face jail time, while those who are addicted to drugs or who have been abused by them are sent to facilities for social and medical rehabilitation. However, it is often found that addicts experience a relapse after carrying out medical and social rehabilitation. When it comes to keeping drugs users from relapsing, religious rehabilitation is superior to medical and social rehabilitation. This study was carried out with a sociological juridical methodology. Purposive nonrandom sampling was the method employed for sampling. The data collection was carried out by library and field studies (through observation, questionnaires and interviews) of the authors and book users. Data analysis was performed using qualitative descriptive analysis. There is a gap in the motivation to resume drug use to shortcomings in medical and social recovery. Additionally, treating addicts with a religious approach that touches their hearts makes them less likely to hesitate to take drugs in the future.